Accuracy of Non-Contact Infrared Thermometer Results with Digital Axillary Thermometers in Infants at Pejeruk Public Health Centers - Gifari, Lalu Maulana Azmi; Wiguna, Putra Aditya; Indriyani, Sang Ayu Kompiyang; Parwata, Wayan Sulaksmana Sandhi; Haq, Abiyyu Didar (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
In Public Health Centers, measuring an infant's body temperature with an axillary digital thermometer often causes discomfort and requires a considerable amount of time to obtain an accurate reading. Non-contact infrared thermometers could offer a suitable alternative due to their quick and portable nature. This study aims to evaluate the accuracy of temperature measurements between non-contact infrared thermometers and axillary digital thermometers for infants, conducted at the Pejeruk Public Health Center. The study employed an observational analytical design, with axillary digital thermometers serving as the gold standard for measurements. Temperature readings were taken from 62 infant participants. The results revealed an Intraclass Correlation Coefficient (ICC) below 0.50, indicating poor accuracy, and a wide agreement limit on the Bland-Altman plot. Therefore, it can be concluded that there is inadequate accuracy between the temperature measurements obtained using the non-contact infrared thermometer and the axillary digital thermometer.